2004
DOI: 10.1074/jbc.m311135200
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Capacitative Calcium Entry in HL-60 Cells by Nanosecond Pulsed Electric Fields

Abstract: Nanosecond pulsed electric fields (nsPEFs) are hypothesized to affect intracellular structures in living cells providing a new means to modulate cell signal transduction mechanisms. The effects of nsPEFs on the release of internal calcium and activation of calcium influx in HL-60 cells were investigated by using real time fluorescent microscopy with Fluo-3 and fluorometry with Fura-2. nsPEFs induced an increase in intracellular calcium levels that was seen in all cells. With pulses of 60 ns duration and electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
157
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 225 publications
(164 citation statements)
references
References 36 publications
6
157
1
Order By: Relevance
“…In Jurkat cells, Scarlett et al [15] observed a fast, field dependent release of calcium only from intracellular stores, mainly the endoplasmatic reticulum for 60 ns pulses at 25 kV/cm and 50 kV/cm, most probable by charging and affecting intracellular membranes. At higher field strength, 100 kV/cm, the increase in free cytosolic calcium was due to internal calcium release and to an influx of calcium across the cell membrane indicating the onset of an impact of plasmamembrane electroporation [39]. It is reasonable, that a nsPEF exposition on plant cells causes similar effects.…”
Section: Resultsmentioning
confidence: 63%
“…In Jurkat cells, Scarlett et al [15] observed a fast, field dependent release of calcium only from intracellular stores, mainly the endoplasmatic reticulum for 60 ns pulses at 25 kV/cm and 50 kV/cm, most probable by charging and affecting intracellular membranes. At higher field strength, 100 kV/cm, the increase in free cytosolic calcium was due to internal calcium release and to an influx of calcium across the cell membrane indicating the onset of an impact of plasmamembrane electroporation [39]. It is reasonable, that a nsPEF exposition on plant cells causes similar effects.…”
Section: Resultsmentioning
confidence: 63%
“…Compared to traditional electroporation, nsPEFs preferentially charge the membranes of subcellular organelles, thereby inducing distinct effects on cellular structure and function that are predominantly intracellular in nature [1,2,5,8]. The resulting delayed plasma membrane permeabilization was likely secondary, arising due to subcellular effects [2] rather than direct electroporation [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Increased permeabilization of the plasma membrane, typically demonstrated by measuring propidium iodide (PI) uptake, due to nsPEFs was delayed compared to traditional electroporation [5,6], indicating that it was an indirect effect. These nsPEFs induced cellular calcium release [7,8] and apoptosis in cells [9,10] or tumors [11,12]. These effects appeared to be due to the charging of interior organelle membranes and the ensuing creation of nanopores.…”
mentioning
confidence: 99%
“…Previous work from this laboratory found that fibrosarcoma tumors treated in vivo with ten 300 ns pulses exhibited a reduced growth rate compared to control tumors in the same animal [6]. Here, we report that when melanoma tumors are treated with four hundred of these pulses, tumors shrink by 90% within two weeks and a subsequent treatment can result in complete remission.The main characteristics of these nanosecond pulsed electric fields (nsPEF) are their low energy that leads to very little heat production and their ability to penetrate into the cell to permeabilize intracellular organelles [7,8] and release calcium [9][10][11] from the endoplasmic reticulum [11]. They provide a new approach for physically targeting intracellular organelles with many applications, including the initiation of apoptosis in cultured cells [12][13][14] and tumors [6], enhancement of gene transfection efficiency [13,14], and inhibiting tumor growth [6].…”
mentioning
confidence: 99%